The Concept of Recycled Farming According to Dayak Kanayatn and the Cultural Dimension - Dismas Kwirinus; Petrus Yuniarto (International Journal Ethnic, Racial and Cultural Heritage, 2023)
This research focuses on explaining the concept of recycled farming according to Dayak Kanayatn and its Cultural Dimensions. Talking about the Dayak Kanayatn cannot be separated from all their life activities. One of their most significant life activities is the farming practices of the Dayak Kanayatn tribe, which is rich in ritual ceremonies. The ceremony signifies the human relationship with nature and all its contents. Apart from that, the activities of the Kanayatn Dayak tribe, which are also essential to discuss, are economic activities. Supported by natural conditions, the Dayak people depend on the recycling farming system for their economy. However, the problem that arose later was the recycling farming system of the Dayaks, who were accused of destroying nature, encroaching on forests, and illegal loggers, thus disturbing and destroying nature. If we open history again, the Dayak tribe has managed nature in this way for centuries but has not caused any damage to nature. Departing from this accusation, the researcher explains how the Dayak Kanayatn people wisely manage nature with recycled farming. This paper aims to respond to accusations of Kanayatn Dayak as natural destroyers of their farming system. Then he wanted to explore one of the cultures of the Dayak people, especially the Kanayatn Dayak, which was almost extinct due to the times. Furthermore, it introduces the Dayak-style culture of nature management through the recycled farming tradition the Kanayatn Dayak represents. The author uses qualitative research methods and critical reading of the text without ignoring the author’s experiences and observations as a Dayak son. The findings of this paper are that the Dayak Kanayatn farming system not only reveals economic activity but also reveals community socio-cultural and religious activities. From how they work the fields with the balale’ system, it is implied that they are solid in solidarity with others. It was there that their solid community life was revealed based on kinship and brotherhood.